The Good Business of Inclusion: A reflection towards a more ethical enactment of business (2009)
With the purpose of crafting a coherent argument in favor of more business inclusiveness, this paper explores the convenience of a wellaccepted model for Corporate Social Performance. After a detailed examination of all its parts, two ethical perspectives –utilitarianism and deontology- are adopted as prisms to evaluate the compatibility of the model with sound moral thinking. At the end, a model of ethical funneling is proposed as a means to enhance business inclusion and performance.